2003
DOI: 10.2960/j.v31.a20
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of the Upper Slope Demersal Community in the Eastern Mediterranean: Preliminary Comparison Between Two Areas With and Without Trawl Fishing

Abstract: Univariate diversity indices and multivariate analyses (cluster and multidimensional scaling (MDS) were performed in order to evaluate biodiversity in two neighbouring areas of the Eastern Mediterranean with different fishing intensity. Data were collected from two trawl surveys (July and August 2000) in two areas of the Ionian Sea. In the area off the South-eastern Italian coast, there is a trawl fishery at depths between 300 and 700 m that targets the deep-sea shrimps Aristeus antennatus and Aristaeomorpha f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 15 publications
(14 reference statements)
11
50
2
2
Order By: Relevance
“…This might be due to the absence of fishing pressure in this area below 400-500 m in depth (D'Onghia et al, 2003). However, according to these authors, the differences in the ichthyofauna composition and abundance between the eastern and western Ionian upper slope could also be due to the different hydrographic conditions on the two sides of the basin.…”
Section: Mora Moromentioning
confidence: 83%
“…This might be due to the absence of fishing pressure in this area below 400-500 m in depth (D'Onghia et al, 2003). However, according to these authors, the differences in the ichthyofauna composition and abundance between the eastern and western Ionian upper slope could also be due to the different hydrographic conditions on the two sides of the basin.…”
Section: Mora Moromentioning
confidence: 83%
“…This latter aspect was particularly evident in the upper and middle slope, where the main differences in the faunistic abundance between the Balearic and Ionian areas were detect-ed. Although the small number of hauls and the gear selectivity could affect the finding of the different species whose abundance appears to decrease with depth, the abundant presence of C. agassizii and H. dactylopterus exclusively on the upper slope of the eastern Ionian Sea might be due to the absence of fishing activity in this area below 400-500 m in depth (D'Onghia et al, 2003). Though on the deepest bottoms the occurrence of some species and their abundance (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…temperature and salinity and productivity) between the western and central Mediterranean (Hopkins, 1989;D'Onghia et al, 2003) have been reported to affect the species distribution (Politou et al, 2004). Few papers discuss the depth distribution of Aristeus in Atlantic waters (Ribeiro-Cascalho, 1988), though the temperature of Atlantic deep-sea waters decreases several degrees below that of Mediterranean waters, where temperature is constant between 12.8 and 14.1 ºC.…”
Section: Discussionmentioning
confidence: 99%